They who give from evil : the response of the Eastern Church to moneylending in the early Christian era - Ihssen, Brenda Llewellyn (James Clarke & Co., 2013)
The purpose of They Who Give from Evil is to consider the financial and salvific implications of usury on the community and the individual soul as it is addressed within the sermons of a selection of early Christian Greek authors, in the historical context of the fourth century Roman Empire. Although focusing on two Greek texts, St. Basil's Homily on Psalm Fourteen and Against Those Who Practice Usury by St. Gregory of Nyssa, Ihssen is able to shed fascinating insight on Roman life and illustrate the rich social justice theologies of the patristic world.